Pengelolaan Dana Desa dan Kebijakan Desa Terhadap Kesejahteraan Masyarakat (Studi Pada Desa Padangbulia Kecamatan Sukasada) - Luh Putu Kharisma Dewi; I Putu Arya Dharmayasa (Universitas Pendidikan Ganesha, 2025)
This study aims to determine (1) the effect of village fund management on community welfare, (2) the effect of village policies on community welfare, and (3) the combined effect of village fund management and village policies on community welfare. The study population consisted of 1,258 households in Padangbulia Village. A Purposive Sampling technique was used, resulting in a sample size of 93 respondents. Data collection was conducted using a questionnaire, and the data were analysed using multiple linear regression. The hypothesis testing involved partial hypothesis testing (t-test) and simultaneous hypothesis testing (F-test), which were processed using SPSS version 25. The results of the study indicate that (1) village fund management has a positive impact on community welfare, (2) village policies have a positive impact on community welfare, and (3) both village fund management and village policies have a simultaneous impact on community welfare.